META ANALISIS: DETERMINAN EARNINGS RESPONSE COEFFICIENT PADA BEBERAPA PENELITIAN SKRIPSI DI INDONESIA - Carmel Meiden; Chyntia Susanto; Helen Leonora (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2022)
Investors need information, one of which is the company's accounting profit figures shown in its financial statements, to make investment decisions. The information is good or bad news that generates various investor responses, and underlies the earnings response coefficient research. Research on the determinants of earning response coefficients has been widely carried out with different research results. This study aims to organize and find the consistency of the results of previous studies. The object of the research is a thesis on the determinants of earning response coefficient with a research period of 2011-2019. The data collection technique used is the observation technique and the sample selection technique used is the purposive sampling technique, and uses meta-analysis as a research analysis technique. The results of this study indicate that earnings persistence, capital structure, firm size, corporate social responsibility disclosure, profitability, and leverage affect the earning response coefficient.